Vidding: Remix as Affective Media Literacy - Stein, Louisa (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2014)
This essay explores the relationship between contemporary remix culture and inherited traditions of fan authorship: more specifically, fan-created music videos or “vids” and the practice of vidding. Through the individual and collective process of vidding, fans showcase their own media literacy, educate their viewers about how to read media, and demonstrate how to engage with and speak back to media and culture. Vids model an affective transmedia literacy, a mode of reading that is simultaneously investigative, critical, and engaged.